Bird communities in two fragments of semideciduos forest in rural São Paulo state - Pozza,D. D. (2003)
A quali-quantitative survey was done in two fragments (75 and 100 ha) of semideciduous forest in rural São Paulo State. The aim was to characterize the bird community according to richness, abundance, and occurrence frequency in these areas. The qualitative survey showed 145 species in the Estação Ecológica de São Carlos - EESCar (Brotas) - and 173 in the Fazenda Santa Cecília - FSC (Patrocínio Paulista), while the quantitative survey showed the presence of 60 and 72 species in EESCar and FSC respectively. The isolation and the lower environmental quality of the EESCar fragment may be responsible for the lower number of species in this area compared to that of FSC. Abundance index value analysis (IPA) showed that both areas have a large number of species with low IPA and few species with intermediate or high IPA compared to the pattern observed in other surveys. At FSC, a larger number of occurrences of species in danger of extinction in São Paulo State was also observed. Apparently, the FSC fragment had better environmental quality for sheltering a larger number of species, including the endangered ones. The study of the community of birds is important in planning management and conservation of natural areas.